Methane dynamics from a mixed plantation of north China: Observation using closed-path eddy covariance method - Yuan, Wenwen; Huang, Hui; Zhang, Jinsong; Meng, Ping; Li, Jun; Wu, Tonggui; Zhou, Fang; Pan, Qingmei (Frontiers in Plant Science, 2023)
Although an important greenhouse gas, methane flux in hilly forest ecosystems remains unclear. By using closed-path eddy covariance systems, methane flux was measured continuously from 2017 to 2019 in a mixed plantation in the Xiaolangdi area of the Yellow River in North China. The methane flux footprint and its diurnal and monthly variations were analysed, and its characteristics on rainy days are discussed. The results showed that: (a) the observation data were reliable with good spatial representation (b) The methane flux in the mixed plantation ecosystem had obvious diurnal and seasonal variations: the monthly average diurnal variation of the methane flux had a single-peak; the methane flux value was source in the daytime and sink at night. The daily mean maximum value of methane flux in growing season was lower than that in non-growing season with the maximum value appearing in March, and the minimum value in October. (c) The forest is an atmospheric CH4 source with the annual emission in 2017 of (3.31 g C·m-2·year -1) >2019 (2.94 g C·m-2·year-1) >2018 (2.81 g C·m-2·year -1), and the main influencing factor was precipitation. Rainfall affected CH4 flux with a lag period of approximately three days. Rainfall also changed the balance of CH4 flux between sink or source according to precipitation intensity and frequency.